LEGAL REVIEW OF THE PROVISIONS OF ARTICLE 97 OF THE KHI ON THE DIVISION OF JOINT PROPERTY BASED ON THE CONCEPT OF BENEFIT - M. Arif Sani; Mhd Azhali Siregar; Andoko, Andoko (PT. Sinergi Legal Publisher, 2025)
Article 97 of the KHI regulates the division of joint property after divorce, which states